Effect of muscle torques ratios and age category on judo fight - Sterkowicz, S.; Lech, G.; Chwala, W.; Sterkowicz-Przybycien, K.; Ambrozy, T.; Palka, T. (Archives of Budo Conference Proceedings, 2015)
Background and Study Aim. The review of the studies that have examined fitness preparation of judokas shows that both dynamic and static strength testing protocols have been in use in judo. Therefore, it can be assumed that strength is an important component of athletes` motor preparation. The principal aim of the present study was to find proportions between relative muscle torques at each stage of athletes` development. Material and Methods. The examinations involved e.g. biometric measurements (BH - body height,BM - body mass) and evaluation of body composition (LBM - lean body mass, FM - fat mass, PF - percentage fat content [12]. Body height was measured with Martin type anthropometer. Results. The authors found that the ratios of relative muscle torques that define the position of the elbow, arm and trunk joints correlated with age of the judokas. We also observed a specificity of the judo fight and demonstrated the differences in the level of the indices of activity and effectiveness of attack depending on the age category. Ratios of the muscle torques measured under static conditions correlated with the indices of the course of the fight to different extent and they were in correlation with the age category. The level of achievement in judo tournaments in junior and cadet categories correlated mainly with the ratio of muscle torques in knee extensors to flexors. Lean body mass was calculated by deducting fat mass. Conclusions. The obtained information might help coaches modify strength training regimes in cadet judokas in order to match model levels of ratios of relative muscle torques observed in seniors under static conditions. Biomechanical characteristics of professional athletes might be of importance to both coaches and scientists in the field of robotics.